Phenotypic variability in faba beans collections from the Valley Toluca-Atlacomulco, Mexico - Salazar Laureles, María Elena; Perez López, Delfina de Jesús; González Huerta, Andrés; Vázquez García, Luis Miguel (Revista Mexicana de Ciencias Agrícolas, 2019)
This study was conducted in the spring-summer 2014 cycle in San Mateo Atenco, Mexico State, Mexico, with the objective of estimating variance and heritability components in 39 faba bean cultivars and identifying outstanding genetic material from quantitative traits and qualitative. A randomized complete block design with three replications was used. The qualitative characteristics were described according to the technical guide for the varietal description in faba bean of the national service of inspection and certification of seeds (SNICS). The results showed statistical significance (p≤ 0.01) among cultivars for each quantitative characteristic. Heritability in the broad sense varied from 30.7 to 99%. The highest seed yield was recorded in the collections identified as T8 (4.16 t ha-1), T5 (3.9 t ha-1) and T 27 (3.8 t ha-1). The principal components analysis explained 65.2% of the original total variation and in this it was observed that the yield correlated positively and significantly with number of pods, pod weight and seed weight. In the cluster analysis four groups were formed, of which the third of these included the faba bean populations with the best agronomic descriptors evaluated.
Keywords: Vicia faba L.; analysis of morphological and agronomic characters; High Valleys of Central Mexico; multivariate analysis